Comparison of Dynamic Hip Screw and Proximal Femoral Nail in Cases of Unstable Intertrochanteric Fractures of the Femur, in Terms of Blood Loss and Operative Time: Experience in a Tertiary Care Hospital - Khan, Ahmed Mustaq; Anwar, Syed Faraz; Saif, Anas Bin; Jaffary, Asad Ullah; Rathore, Muhammad Omar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare Dynamic Hip Screw with Proximal Femoral Nail in unstable Inter Trochanteric femur fractures.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Orthopaedic Surgery, Combined Military Hospital, Malir Pakistan, from Dec 2020 to Aug 2021.Methodology: This study comprised patients aged 40 to 80 years with unstable inter Trochanteric proximal femoral fractures (AO Classification 31A2, 31A3). These patients were randomised into two Groups. Group-A patients underwent Dynamic hip screw fixation, and Group-B patients were subjected to Proximal Femoral Nailing. Follow-up was done at 2,6,12 weeks postoperatively. Two variables, namely operative time and blood loss, were evaluated. Result: Thirty patients were recruited in this study, with 18 patients in each Group. The average blood loss for Group-A Dynamic Hip Screw was measured to be 193.3±29.10 ml, and for Group-B Proximal Femoral Nail was 79.44±17.98 ml (p< 0.001). Group-A (DHS) scored an average operative time of 51.56±7.76 min, and Group-B Proximal Femoral Nail was 36.89±3.66 min (p